Determinants of Choice of Joint Venture Arrangements for International Marketers - Uzoma, Ifediora Chuka; Pius, Ugwoke; Ifeoma, Ifediora Raluchukwu (International Journal of Small and Medium Enterprises, 2019)
This study investigated the determinants of the choice of joint venture arrangements for international marketers in Nigeria. The study aims at identifying the most significant influences on the choice of joint venture arrangements. The survey research design was used for the study. The study was carried out in South-east, Nigeria. A sample of 50 experienced international marketers was selected for the study using a snowball sampling technique. Data was gathered through the use of a structured questionnaire.. The analysis was done using Principal Component Analysis. Findings reveal that brand name/equity, firm size, market attractiveness, research and development, as well as internationalization strategy are the most significant determinants of the choice of joint venture arrangements which international marketers in Nigeria adopt. The study recommends that prospective international marketers consider these factors before or when seeking an alliance with any foreign company an international markets.